2024
DOI: 10.1002/slct.202303356
|View full text |Cite
|
Sign up to set email alerts
|

CuWO4 Reinforced Co‐doped HAp Nanocomposite: Improved Photocatalytic Activity Towards Degradation of Eosin Y and Catalytic Activity in Crossed Aldol Condensation Reaction

Juri Kalita,
Adrija Bose,
Debarati Chakraborty
et al.

Abstract: Preventing the recombination of photoinduced charge carriers in different semiconductor photocatalysts is crucial but high‐performance photocatalyst is still challenging. Herein, we report the synthesis of a novel heterojunction of cobalt‐doped hydroxyapatite with CuWO4 i. e. Co‐HAp@CuWO4 nanocomposite by simple and facile ultrasonication technique. The morphological and structural features of the composite was examined using PXRD, FTIR, SEM, EDS, TEM, UV‐DRS and XPS techniques. The optical analysis showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Thus, these modifications also have a considerable impact on the biological response of doped HAp, both in vitro and in vivo . 5 To date, different research groups have reported the synthesis of doped-HAp materials and utilized such materials in a variety of fields including medicine, 6 catalysis, 7 photocatalysis, 8 bone tissue engineering, 9 drug delivery 10 and so on. Out of these, photocatalysis is one of the most widely explored applications of modified hydroxyapatite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these modifications also have a considerable impact on the biological response of doped HAp, both in vitro and in vivo . 5 To date, different research groups have reported the synthesis of doped-HAp materials and utilized such materials in a variety of fields including medicine, 6 catalysis, 7 photocatalysis, 8 bone tissue engineering, 9 drug delivery 10 and so on. Out of these, photocatalysis is one of the most widely explored applications of modified hydroxyapatite materials.…”
Section: Introductionmentioning
confidence: 99%